Analysis of serum calcium, sodium, potassium, zinc, and iron in patients with pre‐eclampsia in Bangladesh: A case–control study. Issue 2 (2nd February 2023) - Uddin, S. M. Naim; Haque, Mahmodul; Barek, Md Abdul; Chowdhury, Mohammad Nizam Uddin; Das, Abhijit; Uddin, Md. Giash; Islam, Mohammad Safiqul
Abstract: Background and Aims: Pre‐eclampsia is a particular type of pregnancy condition. Although the primary etiology of pre‐eclampsia is unclear, it hypothesizes that the alteration of trace elements and macro‐minerals may play a crucial function in the pathogenesis of Pre‐eclampsia. Therefore, our research sought to ascertain the serum level of trace elements (zinc, iron) and macro‐minerals (sodium, calcium, potassium) and their possible association with pre‐eclampsia. Methods: The present study was conducted with 74 pre‐eclampsia pregnant women (case) and 118 pregnant women having normal blood pressure (controls). Atomic Absorption Spectroscopy determined the serum level of trace components and electrolytes. Results: The researchers discovered notable differences in maternal age, gestational period, body mass index, systolic and diastolic blood pressure, hemoglobin, and creatinine level. Results of serum analysis revealed that calcium (52.06 ± 3.71 mg/L vs. 65.93 ± 2.57 mg/L, p  < 0.05) and potassium (63.44 ± 5.33 mg/L vs. 102.54 ± 4.25 mg/L, p  < 0.001) concentrations were substantially lower in the patient group than in control. Serum zinc (0.34 ± 0.02 mg/L vs. 0.52 ± 0.02 mg/L, p  < 0.001) and iron (0.38 ± 0.03 mg/L vs. 0.46 ± 0.02 mg/L, p  < 0.05) concentration were also considerably decreased in pre‐eclampsia participants compared with a pregnant normotensive group. Pearson's correlation research results in the patient group revealed a connection between trace elements or macro minerals. In addition, the systolic blood pressure was positively correlated with sodium ( r  = 0.392, p  < 0.01) and negatively correlated with potassium ( r  = −0.257, p  < 0.05) in the control group. Conclusions: This study concludes that calcium, potassium, iron, and zinc levels were lower, whereas sodium levels were higher in Bangladeshi pre‐eclampsia patients compared to controls. These findings with Pearson's correlation and the inter‐element relationship between the patient and a control subject results can act as critical indication factors for patients with pre‐eclampsia in Bangladesh and, as a result, may require a higher intake of calcium, potassium, iron, and zinc for effective therapeutic intervention and reduce the intake of sodium.